2016
DOI: 10.3382/ps/pew241
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation with a probiotic (Enterococcus faecium) on production performance, excreta microflora, ammonia emission, and nutrient utilization in ISA brown laying hens

Abstract: The ban on the use of antibiotics as growth promoters due to resistance issues has urged scientists to find alternatives to antibiotics. Entercoccus faecium is one of the probiotics which have been used as an alternative to antibiotics in the livestock industry. This study was conducted to evaluate the effect of probiotic (Enterococcus faecium DSM 7134) supplementation on production performance, feed intake, egg quality, excreta microflora, ammonia emission, and nutrient utilization in laying hens. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 29 publications
3
47
0
Order By: Relevance
“…Increasing consumer awareness about food safety has lead the poultry industry to find alternatives to antibiotic growth promoters . Therefore, banning antibiotic growth promoters creates new challenges for animal scientists with respect to finding alternatives to antibiotics . As a result, researchers are looking for a proper alternative to antibiotics from natural feed resources to promote the growth and health status of animals, as well as poultry, that is both environmentally friendly and safe for humans.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing consumer awareness about food safety has lead the poultry industry to find alternatives to antibiotic growth promoters . Therefore, banning antibiotic growth promoters creates new challenges for animal scientists with respect to finding alternatives to antibiotics . As a result, researchers are looking for a proper alternative to antibiotics from natural feed resources to promote the growth and health status of animals, as well as poultry, that is both environmentally friendly and safe for humans.…”
Section: Introductionmentioning
confidence: 99%
“…Low levels of E. faecium were reported in unwashed eggs and 10% salted LEY (Imai, ). Park, Jeong, Lee, and Kim () showed that using E. faecium as a probiotic dietary supplement as an alternative to antibiotics improved nutrient digestibility, increased egg production, and reduced fecal coliform counts and excreta ammonia emission in ISA brown laying hens. Feeding hens with E. faecium as a probiotic reduced cholesterol in egg yolk (Angelovičová, Král, Alfaig, & Tkačová, ).…”
Section: Discussionmentioning
confidence: 99%
“…According to Mi et al (2019) lactic acid bacteria could produce more effective acid to reduce ammonia in chicken feces, so the amount of H + ions would be high. H + ions in chicken feces could convert ammonia to ammonium (NH4 + ) so the formation of ammonia emissions by gram-negative bacteria could be prevented (Kabir, 2009;Pezzuolo et al, 2019).. Lactic acid bacteria produce acidand are proteolytic, so they can reduce ammonia by breaking down the protein in uric acid. Lactic acid bacteria utilized uric acid as a nutrient and broke it down to the monomers.…”
Section: Gastrointestinal Microflora and Ammonia In Laying Hensmentioning
confidence: 99%
“…This resulted in decreasing ammonia production because of the availability of uric acid to be converted to ammonia is reduced. Lactic acid bacteria also produced bacteriocin (antibiotics), which suppressed the growth of pathogenic gram-negative bacteria which produced ammonia (Dhama et al, 2011;Park et al, 2016;Chen et al, 2017). This suppression of bacterial growth resulted in decrease of producing the urease enzyme from gram-negative bacteria which used to convert uric acid to ammonia (Mi et al, 2019;Pezzuolo et al, 2019).…”
Section: Gastrointestinal Microflora and Ammonia In Laying Hensmentioning
confidence: 99%
See 1 more Smart Citation